1998
DOI: 10.1002/(sici)1097-0290(19980405)58:1<73::aid-bit8>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chimeric antibody producing CHO cells in the course of dihydrofolate reductase‐mediated gene amplification and their stability in the absence of selective pressure

Abstract: Recombinant Chinese hamster ovary (CHO) cells expressing a high-level of chimeric antibody against S surface antigen of hepatitis B virus were obtained by co-transfection of heavy and light chain cDNA expression vectors into dihydrofolate reductase (dhfr)-deficient CHO cells and subsequent gene amplification in medium containing stepwise increments in methotrexate (MTX) level such as 0.02, 0.08, 0.32, 1.0, and 4.0 microM. The highest producer (HP) subclone was isolated from each MTX level and was characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
80
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 0 publications
2
80
0
Order By: Relevance
“…MTX amplification increased the yield of IgG by up to 75-fold in the case of IS4VH/IS4VL. The variable expression from CHO cells is well documented in both our hands (31) and others (38). This phenomenon occurs during subcloning in successive amplification steps when cells can increase the copy number of the dhfr gene without increasing their production rate (38).…”
Section: Stable Expression Of Whole Igg In Cho Cellsmentioning
confidence: 74%
See 1 more Smart Citation
“…MTX amplification increased the yield of IgG by up to 75-fold in the case of IS4VH/IS4VL. The variable expression from CHO cells is well documented in both our hands (31) and others (38). This phenomenon occurs during subcloning in successive amplification steps when cells can increase the copy number of the dhfr gene without increasing their production rate (38).…”
Section: Stable Expression Of Whole Igg In Cho Cellsmentioning
confidence: 74%
“…The variable expression from CHO cells is well documented in both our hands (31) and others (38). This phenomenon occurs during subcloning in successive amplification steps when cells can increase the copy number of the dhfr gene without increasing their production rate (38). Thus, cells that do not produce an exogenous protein will usually have a higher growth rate and take over the culture, thereby reducing the chance of selecting a high producer cell.…”
Section: Stable Expression Of Whole Igg In Cho Cellsmentioning
confidence: 89%
“…In general the degree of gene amplification is proportional to the level of gene expression (Guarna et al, 1995;Jiang et al, 2006;Pendse et al, 1992). However, high gene copy numbers do not always result in high productivity, probably the result of transcriptional and post-transcriptional limitations in highly amplified subclones (Kim et al, 1998b;Lattenmayer et al, 2007). Gene amplification and high-level expression of a foreign gene product can challenge the cells with different levels of toxicity and metabolic burden.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies addressing this issue a loss in transgene copy numbers was reported to be the major cause for the decrease in recombinant protein productivity (Fann et al, 2000;Hammill et al, 2000;Kim et al, 1998a,b;Pallavicini et al, 1990). In some cases, no decrease in transgene copy numbers was observed and decreased transcriptional efficiency was discussed to be the reason for the decline in productivity (Kim et al, 1998b). The chromosomal site of integration of a recombinant gene has a major effect on its transcription rate, a phenomenon called the ''position effect'' (Wilson et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed understanding of how cells regulate this pathway is a prerequisite for designing genetic strategies for increasing antibody production [1]. Methotrexate (MTX), which is widely used in the creation of high-producing stable cell lines by amplification of gene copy number, provides an effective means to alter Mab production rates for mechanistic studies of the regulation of this pathway [2]. …”
mentioning
confidence: 99%